Melorrealismo global: una tendencia estética cinematográfica contemporánea - Narváez, Geovanny (Ñawi, 2022)
This study proposes an extrapolation of the aesthetic typology known as melodramatic realism. This approach, based on a corpus that includes Linha de passe (2008), Leonera (2008), Biutiful (2010), El niño (2005), Precious (2009) and Cafarnaúm (2018), seeks to illustrate a trend of global melodramatic realism in contemporary cinema through the identification of five main tropes: realistic effect in fiction, the cartography of adversity and belonging, social commitment and/or protest, personification of vulnerability and exaggeration.